The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1017/s0954579417000608
|View full text |Cite
|
Sign up to set email alerts
|

Social–ecological predictors of externalizing behavior trajectories in at-risk youth

Abstract: Extant research consistently links youth externalizing problems and later maladaptive outcomes, and these behaviors are particularly detrimental given their relative stability across development. Although an array of risk and protective factors for externalizing problems have been identified, few studies have examined factors reflecting the multiple social-ecological levels that influence child development and used them to predict longitudinal trajectories of externalizing problems. The current study examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 103 publications
0
14
0
Order By: Relevance
“…Shared family adversities (e.g., family relationship and health stressors) may have contributed to emerging comorbid conditions in both classes. Other variables that were not assessed in this study, such as peer relationships (Figge et al, 2018) and academic functioning, may also partly explain why externalizing behavior remits for the HCL class and emerges later in the AO class.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Shared family adversities (e.g., family relationship and health stressors) may have contributed to emerging comorbid conditions in both classes. Other variables that were not assessed in this study, such as peer relationships (Figge et al, 2018) and academic functioning, may also partly explain why externalizing behavior remits for the HCL class and emerges later in the AO class.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the recent findings of Figge et al (2018), research suggests that children who follow the CL and AO trajectories typically have somewhat similar patterns of childhood risks. Their marked variability in externalizing outcomes has thus led Barker, Oliver, and Maughan (2010) to speculate that these two groups may differ in risk exposure as they approach adolescence.…”
Section: Variations In Risk Factors Across Trajectory Groupsmentioning
confidence: 95%
See 2 more Smart Citations
“…Several studies have employed group-based trajectory approaches to identify distinct latent trajectories of internalizing and externalizing outcomes through development. Although age ranges vary, studies typically identify five externalizing trajectories, each with a large proportion of the sample displaying a low level of externalizing behavior, and a stable moderate or medium group, a decreasing group, an increasing group, and a stable high group (Fanti & Henrich, 2010; Figge et al, 2018; Haltigan et al, 2011; Nivard et al, 2017). Five similarly shaped trajectories have been found in studies on internalizing symptoms (Nivard et al, 2017), although a study of internalizing behavior from ages 2 to 12 identified three stable trajectories (low, moderate, and high; Fanti & Henrich, 2010).…”
Section: Aces and Externalizing And Internalizing Outcomesmentioning
confidence: 99%